When Permits Are Missing: Legal Impacts on Apartment Buyers in Non-Compliant Buildings - Hadiputra, Mikko Agustian; Yatulloh, Dina Mukti (Universitas Negeri Semarang, 2024)
The rapid growth of urban areas has driven significant changes in people's housing patterns, especially through the choice of multi-storey housing. This phenomenon emerged as a response to land limitations and high population mobility in urban areas. Behind all the conveniences conveyed in commercial offers, vertical housing is not free from complex problems, both in the legal realm and in daily management practices. Disputes between residents and managers, imbalances in the enforcement of rights and responsibilities, and weak guarantees of legal certainty in unit ownership transactions are issues that often arise. This article attempts to examine the normative framework and the reality of its implementation in the context of multi-storey housing in Indonesia. With a juridical-empirical approach, the discussion focuses on the aspect of legal relations between the parties involved and the urgency of policy reformulation in order to create a more inclusive and equitable management system.